A proposed scenario for the partnership between Ministry of Education and the third sector in training secondary school teachers on skills the twenty-first century in the light of global experiences - Al-Qahtani, Mashael Abdullah Ayed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to formulate a proposed vision for activating the partnership between the Ministry of Education and the third sector in training secondary school teachers on twenty-first century skills in the light of global experiences, revealing the requirements for its activation, and the most prominent obstacles to its activation. It was distributed to a stratified random sample of (283), including (197) male and female supervisors in the regions of (Makkah Al-Mukarramah - Tabuk - Riyadh - Eastern Province - Najran); In addition to (86) male and female administrators from the third sector employees in the same regions; The results of the study showed that the reality of the partnership between the Ministry of Education and the third sector in training secondary teachers came with a total average of (3.95 out of 5); To a (significant) degree, as the results showed the agreement of the study sample on the requirements of activating the partnership with an average of (4.21); degree (strongly agree); The obstacles to activating the partnership came at an average of (4.12); to a (significant) degree, most notably in the existence of an information gap between the Ministry of Education and third sector institutions; based on the results; The researcher presented a proposed vision to activate this partnership. It includes: the philosophy of the proposed vision, its principles, justifications, objectives, requirements, fields, mechanisms and procedures for its implementation, obstacles to its implementation, ways to confront obstacles to the implementation of the proposed vision, in addition to proposals for complementary studies on the subject.